2023
DOI: 10.1021/acs.jpcb.3c01574
|View full text |Cite
|
Sign up to set email alerts
|

Scaling Properties of Liquid Dynamics Predicted from a Single Configuration: Small Rigid Molecules

Abstract: Isomorphs are curves in the thermodynamic phase diagram along which structure and dynamics are invariant to a good approximation. There are two main ways to trace out isomorphs, the configurational-adiabat method and the direct-isomorph-check method. Recently a new method based on the scaling properties of forces was introduced and shown to work very well for atomic systems [Phys. Rev. Lett.2022129245501]. A unique feature of this method is that it only requires a single equilibrium configuration for tracing o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 36 publications
0
0
0
Order By: Relevance
“…The literature reports on such systems are not frequent and they mainly focus on the rigid molecules, for which generalized version of the isomorph concept has been proposed [157]. It was shown that rigid symmetric dumbbell with IPL potential exhibits strong WU correlation, which however is characterized by the slope value higher than m t /3 [158].…”
Section: γ γ Eos and γ Lj For Quasi-real Particles With Ipl Potentialmentioning
confidence: 99%
“…The literature reports on such systems are not frequent and they mainly focus on the rigid molecules, for which generalized version of the isomorph concept has been proposed [157]. It was shown that rigid symmetric dumbbell with IPL potential exhibits strong WU correlation, which however is characterized by the slope value higher than m t /3 [158].…”
Section: γ γ Eos and γ Lj For Quasi-real Particles With Ipl Potentialmentioning
confidence: 99%